DEVELOPMENT OF TECHNOLOGY TO INCORPORATE DEHYDRATED MURUNGA LEAF POWDER IN PANEER CHEESE - Samadiy, Murodjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. Murunga (Moringa oleifera) is a popular plant and the leaves and fruits are very famous for food but it is underutilized in Sri Lanka even though it has some functional properties. It has some essential oil fractions which provide functional properties. This study was carried out to develop a technology to incorporate Murunga leaf powder in paneer cheese and analyze the chemical and microbial composition, and its’ acceptability using (soft and hard paneer). Preparation of paneer was done in a usual way and citric acid was used as a coagulant for all treatments and treated with 0.50, 1.00, 1.50, and 2.00% of Murunga leaf powder for this experiment named T1 to T4 respectively. Sensory analysis was conducted (30 panelists) by using hedonic scale (5-point) to evaluate the acceptance level of Murunga incorporation in paneer. Methods. Cow milk was used for this experiment and fat, and solid non-fat of that milk were analyzed using the Gerber method and standard equation to find Solid non-fat. To produce quality paneer cheese it is recommended to add 0.08-0.15% of (CaCl2) Calcium chloride into the milk to induce coagulation. Results. The study was conducted to characterize the paneer by having chemical analysis of the Murunga leaf powder incorporated paneer made with different percentages. The protein contents were analyzed just after 10th, 20th, and 30th days in ambient conditions. It shows that there were no significant differences in the protein percentages but slight rises were observed in pH, reduction in the total plate counts with Murunga leaf powder added paneer sample compared with control. Also, coliform counts were not observed throughout the storage period but the sensory analysis showed that the flavor, color, odor and overall acceptability of samples were found significantly different (P<0.05). This illustrates that the Murunga leaf powder incorporated paneer has high acceptability and could be potentially used as a functional ingredient, especially for antimicrobial activity, extending the shelf life and increasing the antioxidant ability in paneer and T3 was selected as the best percentage for paneer cheese. Conculusion. Dehydrated Murunga leaf powder added to paneer has high acceptability especially T3 is identified as the best percentage. Also, it has effects on self-life improvement of paneer due to the inhibitory effect against microbes. Therefore, Murunga leaf powder could be used as a preservative in dairy products. The amount of Murunga leaf powder (1.5%) could be considered the acceptable amount for paneer cheese production.